Frequency and Outcomes of Hepatorenal Syndrome in Patients with Chronic Liver Disease - Sarwar Khan, Kapeel Raja, Muzzamil Riaz Malik, Sohail Hussain, Khalil Ur Rehman, Hira Tahir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of hepatorenal syndrome in patients presented with chronic liver disease, also examine one month mortality in patients diagnosed with hepatorenal syndrome. Study Design: Prospective/Observation Study Place and Duration: Medical Ward, THQ Hospital Dargai Malakand and Ziauddin University Karachi, From November, 2021 to April, 2022. Methodology: One hundred and five patients of either gender presented with chronic liver disease having ages 18 to 65 years were enrolled. Detailed demographics including age, sex, BMI, duration of disease and etiology of liver cirrhosis were recorded after taking informed written consent. Patients with hepatic encephalopathy being treated with nephrotoxic drugs, acute infection, hypovolemia, sepsis, and fulminant and sub-fulminant hepatic failure were excluded. Serum creatinine was analyzed in all the patients to examine renal failure. Outcomes in term of one month mortality was also examined in HRS patients. Data was analyzed by SPSS 24.0. Results: There were 63 (60%) males while 42 (40%) patients were females with mean age 47.18±11.64 years. Mean BMI was 24.66±3.84 kg/m2. Among 105 patients 15 (14.29%) patients were diagnosed to have hepatorenal syndrome. Out of 15 HRS patients, 4 (26.67%) were died. Conclusion: It is concluded that frequency of hepatorenal syndrome in liver cirrhosis patients was high. And HRS was associated with high rate of mortality. Keywords: Chronic Liver Disease, HBV, HCV, Hepatorenal Syndrome, Mortality